Development of Ethnographic Tourism in the Republic of Tuva - SAMBUU, Anna (Journal of Environmental Management and Tourism, 2020)
Tuva has a huge tourist potential, combining a unique variety of natural conditions with picturesque landscapes, richness of fauna and flora, preserved national traditions, unique monuments of nature and culture. Pristine nature, a large number of natural and archaeological sites, extensive hunting grounds – all this creates the basis for the development of domestic and international tourism in the region. The ancient history and diversity of natural conditions of the mountain area determined the traditional way of life of the Tuvinians, the life of Russian old believers, Buddhism and shamanism, which are of great interest to tourists. However, in the sphere of tourism of the Republic there are problems and limitations associated with the current state of the tourist infrastructure, etc. The purpose of this article is to identify the specifics of the development of ethnographic tourism in the Republic of Tuva, taking into account national and spiritual and moral aspects for the revival and preservation of ethnic and cultural heritage.